2020
DOI: 10.3390/agronomy10091357
|View full text |Cite
|
Sign up to set email alerts
|

An Appraisal of Calcium Cyanamide as Alternative N Source for Spring-Summer and Fall Season Curly Endive Crops: Effects on Crop Performance, NUE and Functional Quality Components

Abstract: A two-year study was conducted in both spring-summer and fall seasons to evaluate calcium cyanamide (CaCN2) as an alternative nitrogen (N) source for curly endive (Cichorium endivia L. var. crispum) grown in a Mediterranean environment. Four types of N applications were administered: (i) pre-transplanting base application of 100 kg N ha−1 corresponding to 100% of the supplied N (100CC), (ii) pre-transplanting base application of 50 kg N ha−1 corresponding to 50% of the supplied N (50CC) complemented with 50 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Our outcomes, also, highlighted that the growing season did not affect SSC. This result is in accordance with the finding of Sabatino et al [28], who did not determine differences in terms of SSC between curly endive plants grown in the fall and those grown in the spring-summer season. Moreover, our outcomes showed that, regardless of the growing season, total phenolics increased as I concentration in the nutrient solution increased.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our outcomes, also, highlighted that the growing season did not affect SSC. This result is in accordance with the finding of Sabatino et al [28], who did not determine differences in terms of SSC between curly endive plants grown in the fall and those grown in the spring-summer season. Moreover, our outcomes showed that, regardless of the growing season, total phenolics increased as I concentration in the nutrient solution increased.…”
Section: Discussionsupporting
confidence: 93%
“…Our outcomes revealed that head fresh weight and stem diameter were not affected by the growing season. On the contrary, Sabatino et al [28] reported that the number of leaves is positively influenced by the fall season in control plants, whereas spring-summer plants treated with 50 mg I L −1 performed better than those cultivated in the fall. Moreover, the number of leaves in spring-summer grown plants treated with 250 or 500 mg I L −1 did not significantly differ from that recorded in the fall grown plants supplied with the same I dosage.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Vegetable production systems need specific agricultural practices [10][11][12] and depend on high quantity of mineral nutrients (especially N, P and K) to enhance growth, yield and quality [13][14][15]. However, the incessant use of artificial fertilizers may pose threats on the ecosystem survival.…”
Section: Introductionmentioning
confidence: 99%
“…The chlorophyll content and the photosynthetic rate are directly related to the mineral content and nitrogen fertilization of vegetables [31,42,43]. The onion is very greedy for nitrogen, and careful management of fertilizer is needed due to the shallow nature of the root system [20] and the risk of nitrogen accumulation both in the soil and the produce [44].…”
Section: Discussionmentioning
confidence: 99%